Detailed analysis of chemical corrosion of ultra-thin wires used in drift chamber detectors. (7th December 2021) - Baldini, A.M.; Cavoto, G.; Cei, F.; Chiappini, M.; Chiarello, G.; Chiri, C.; Cocciolo, G.; Corvaglia, A.; Cuna, F.; Francesconi, M.; Galli, L.; Grancagnolo, F.; et al.
Abstract: Ultra-thin metallic anode and cathode wires are frequently employed in low-mass gaseous detectors for precision experiments, where the amount of material crossed by charged particles must be minimised. We present here the results of an analysis of the mechanical stress and chemical corrosion effects observed in 40 and 50 μm diameter silver plated aluminum wires mounted within the volume of the MEG II drift chamber, which caused the breakage of about one hundred wires (over a total of ≈ 12000). This analysis is based on the careful inspection of the broken wires by means of optical and electronic microscopes and on a detailed recording of all breaking incidents. We present a simple empirical model which relates the number of broken wires to their exposure time to atmospheric relative humidity and to their mechanical tension, which is necessary for mechanical stability in the presence of electrostatic fields of several kV/cm. Finally we discuss how wire breakages can be avoided or at least strongly reduced by operating in controlled atmosphere during the mounting stages of the wires within the drift chamber and by choosing a 25 % thicker wire diameter, which has very small effects on the detector resolution and efficiency and can be obtained by using a safer fabrication technique.